DIFUSI INOVASI PENDIDIKAN MATEMATIKA REALISTIK INDONESIA KEPADA GURU MATEMATIKA SMP DI KABUPATEN SLEMAN MELALUI LESSON STUDY - Bondan Widjajanti, Djamilah; Listyani, Endang; Susanti, Mathilda; Mahmudi, Ali; Sugiman, Sugiman (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2013)
A Community Service activity entitled "Diffusion of Innovations of Indonesian Realistic Mathematics Education to Mathematics Teachers of Junior High School (SMP) in Sleman Regency through Lesson Study" aims at diffusing Innovations of Indonesian Realistic Mathematics Education (Pendidikan Matematika Realistik Indonesia: PMRI) to Mathematics Teachers of SMP in Sleman Regency who are actively participating in SubjectBased Teachers Group (Musyawarah Guru Mata Pelajaran: MGMP) of Mathematics. The diffusion is conducted through Lesson Study. Specifically, this PPM activity aims at improving understanding of mathematics teachers as participants on excellences of PMRI and Lesson Study and increasing teachers' willingness to implement PMRI in the Lesson Study format. Objects of the study were 25 mathematics teachers of SMP in Sleman Regency actively participating in MGMP. The first activity was socialization on PMRI and Lesson Study. It was conducted on July 12, 2012 in the Mathematics Education Laboratory and was joined by 25 participants. The second activity was in a workshop on Development of Learning Tools and the implementation of the plan phase which was conducted on July 26, 2012 in the Mathematics Education Laboratory with 25 participants. Meanwhile, the third activity was the implementation of the do and see phase conducted on August 9, 2012 at SMP Muhammadiyah III Depok Sleman with 25 participants. In the beginning and the end of the activity, all participants were given written questions to reveal their understanding on PMRI and Lesson Study. In the end of the activity, questions were added about advantages of PMRI and Lesson Study. All participants of the activity stated that PMRI and Lesson Study are very advantageous for students and teachers. All of them also committed to implement PMRI in the Lesson Study format. Considering the results above, it can be concluded that this PPM activity is successful to improve the understanding of mathematics teachers as participants on excellences of PMRI and Lesson Study and also works to increase their willingness to implement PMRI in the Lesson study format. In addition, all participants also hope on the follow-up of this activity. Therefore, Department of Education, Youth and Sport of Sleman Regency and UNY (Yogyakarta State University) need to establish cooperation to facilitate the implementation of PMRI in the Lesson Study format for mathematics teachers of SMP in Sleman Regency.Keywords: realistic mathematics education, and mathematics lesson study